Music and dance in respiratory disease management in Uganda: a qualitative study of patient and healthcare professional perspectives - Philip, KEJ; Cartwright, LL; Westlake, D; Nyakoojo, G; Kimuli, I; Kirenga, B; Brakema, EA; Orme, MW; Fancourt, D; Hopkinson, NS; Jones, R; Katagira, W (BMJ, 2021)
Introduction Music and dance are increasingly used as adjunctive arts-in-health interventions in high-income settings, with a growing body of research suggesting biopsychosocial benefits. Such low-cost, low-resource interventions may have application in low-resource settings such as Uganda. However, research on perceptions of patients and healthcare professionals regarding such approaches is lacking.